Only-Child Matching Penalty in the Marriage Market - Keisuke Kawata; Mizuki Komura (Institute of Labor Economics (IZA), 2025)
This study explores the marriage matching of only-child individuals and the related outcomes. Specifically, we analyze two aspects: First, we investigate the marriage patterns of only children, examining whether people choose mates in a positive or negative assortative manner regarding only-child status. We find that, along with being more likely to remain single, only children are more likely to marry another only child. Second, we measure the matching premium or penalty using the difference in partners' socioeconomic status, measured by years of schooling, between only-child and non–only-child individuals. Our estimates show that among women who marry an only-child husband, only children are penalized, as their partners' educational attainment is 0.63 years lower. Finally, we discuss the potential sources of this penalty along with our empirical findings.
Keywords: J11; J12; J16; 330; marriage matching; only children; gender; machine learning